ПРОБЛЕМНОЕ ОБУЧЕНИЕ НА УРОКАХ ХИМИИ - Бектурганова, З.К.; Каипбергенов, А.Т.; Абдуллаева, Н.А. (SCIENCE and SOCIETY, 2019)
The article discusses the stages of problem-based learning about mental activity, the development of cognitive activity, the creative independence of students, the formation of their worldview, contributing to intellectual development.
Keywords: developing concepts; abilities; pedagogical technologies; problem education; mental activity